Pemahaman Siswa-Siswi SD NU Sleman Yogyakarta Terhadap Pelajaran Akhlak Syiir Ngudi Susila Karya KH. Bisri Mustofa (Kajian Resepsi) - Sa'diah, Nur Azizah; Hidayah, Nur (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
Morals are the main goal achieved by every human being which can be done through education. Understanding morals plays a very important role in the process of life. SD NU Sleman Yogyakarta in morals lessons uses the book Syiir Ngudi Susila in class III, a form of example of good morals for students and its strategic value lies in the teaching process and understanding. This research uses descriptive qualitative research. Researchers used four methods, namely interviews, observation, documentation and questionnaires. The moral values contained in the book Syiir Ngudi Susila include: (1) Morals towards Allah SWT; (2) Morals towards parents; (3) Morals towards teachers; (4) Morals towards friends; (5) Morals towards guests/other people; (6) Morals towards brothers; (7) Morals towards oneself. The teacher's reception of the book contains easy moral values which are still basic to be studied in class III. So that students' understanding is contained in 2 values, namely the test question value and the behavior value.